Sistem Informasi Penjadwalan Supir Bus Po Logos Berbasis Website - Zakharia, Zakharia; Widiatry, Widiatry; Sari, Nova Noor Kamala (Universitas Palangka Raya, 2021)
The problem with the PO Logos company is that the schedule for the driver or bus driver is still done manually which results in the old operator determining the bus driver who will depart. And the distribution of the driver's departure schedule is not evenly distributed so that the bus driver who has just departed is scheduled to leave again the next day which causes the driver to contact the operator to report this in order to get a replacement driver, because the rules for drivers at PO Logos company are once every three days. From these problems raised the idea to create a driver scheduling information system for PO Logos. This was built using the Waterfall methodology which consists of 5 stages, namely Requirement Analysis and Definition of the old system analysis and the new system of scheduling using genetic algorithms which are described by flowcharts, System and Software Design using Unifed Modeling Language (UML), Implementation and Unit Testing using programming languages PHP and MySQL, Integration and System Testing Testing is done by black-box testing. The results of making a bus driver scheduling information system in making a driver schedule using a genetic algorithm through stages, namely the formation of the initial population, evaluating the fitness value, finding the two best fitness values ??using tournament selection, crossover using one-point crossover, mutation and fitness evaluation again for looking for the best value.